Obtenção de insumos proteicos de amêndoa de castanha de caju por diferentes rotas e aplicação em produto plant-based - Carmo, Jéssica Silva do (2024)
The development of plant-based products with nutritional quality and well-accepted by consumers has driven the search for alternative vegetable protein sources. Cashew nut stand out for presenting protein considered to be of quality and good technological functionality, besides mild flavor. Oil extraction is an important step when it comes to obtaining protein concentrates from oilseed raw materials. The main oil extraction methods are pressing and solvent extraction. Cold pressing is fast, accessible and economical, involving no heating or addition of chemicals, although it has a lower extraction yield than other methods. Hexane is a solvent widely used in the extraction of vegetable oils due to its high efficiency, but it is known to be highly toxic and flammable, and can leave residues in both the oil and the defatted flour. Aqueous oil extraction is a viable alternative that does not require the use of organic solvents, allowing the simultaneous recovery of oil and protein. The aim of this study was to evaluate the production of protein inputs from cashew nut by alternative methods to the use of hexane for oil extraction and to evaluate their application in the development of a meat analogue product. Defatted flour and protein concentrate obtained from the process using hexane in a Soxhlet apparatus presented higher protein contents, 40.36% and 85.45%, respectively, confirming that this is the most efficient method for oil extraction described in the literature. Pressing process resulted in defatted flour and protein concentrate with 27.40% and 59.34% of proteins, respectively. Aqueous oil extraction had a more advantageous yield than pressing, obtaining defatted flour with 35.51% and protein concentrate with 69.02% of proteins. Protein concentrate derived from the defatted flour by aqueous extraction exhibited interesting functional and technological characteristics, such as better oil absorption and emulsifying capacity. Protein concentrates presented a complete amino acid profile, with lysine being the only limiting essential amino acid, and in vitro digestibility greater than 90%. The applicability of cashew nut protein inputs was evaluated in the development of plant-based nuggets. Plant-based nuggets presented protein contents ranging from 9.54% to 17.97%. Plant-based nuggets prepared with defatted flour by aqueous extraction and pressing presented more than 10% of the daily reference value (DRV) of proteins per serving and an excellent amino acid profile, can be labeled as a "source of proteins". Plant-based nuggets with addition of protein concentrate obtained from defatted flour by aqueous extraction presented more than 20% of the DRV of proteins per serving, but requires adjustments to increase the lysine content. Cashew nut plant-based nuggets had an acceptability higher than 79% and a purchase intention above 70% in the positive zone, demonstrating great market potential. The results indicated that the cashew nut protein inputs showed good applicability in the development of a meat analogue. The choice of processing method is decisive in the composition and characteristics of the products to be developed, making it viable to use alternative methods to oil extraction with hexane.